Effect of Land Levelling on Irrigation Efficiencies and Wheat Yield - Rajput, T.B.S.; Patel, Neelam (Journal of Soil and Water Conservation, 2022)
Proper land leveling is a prerequisite of the practice of intensive agriculture to ensure maintaining high water application, storage and distribution e fficiencies. To achieve high irrigation efficiencies, the irrigation water is to be delivered uniformly across the field with minimum losses through evaporation, deep percolation and runoff. Leveling index (LI) and Land Uniformity Coefficient (LUC) were estimated to assess the smoothness of the land surface of the selected farmers' fields of village Masauta, district Gaziabad, U.P. No direct relationship was found between leveling indices and the size of the fields. When the farmers were categorized as Large, Medium and Small landholders and data of their holding sizes were pooled, strong relationships between the two leveling indices and field size were observed. LI increased but LUC decreased with increasing field sizes. The application, storage and distribution efficiencies in the field having the least leveling index of 1.5 cm were 104.0, 206.25 and 120.5 % higher, respectively, than the field having a high leveling index of 14.1 cm. Good correlation was found between LI (R2=0.896) and LUC (R2 =0.918) with wheat yield. Maximum wheat yield of 5.0 t/ha was obtained from the field with the least LI 1.5 but highest LUC of 0.98, respectively. This is because of better distribution and less loss of irrigation water as reflected by higher irrigation efficiencies. The wheat yield was significantly less in the fields with LI values higher than 3.0 cm and LUC lesser than 0.85, respectively.